(3GdagQSJs - (3GHf GdfOje , eMeO Hf ESMGb Hf eMeO Hf ESMGb , CHh GdaQL Hf CHj jYbhH GdfOje,J (B438 (3g` s ((3jhSa Hf egjGQ Hf efUhQ s)
(3ChdgG (B:s
(3gPG agQSJ cJH GdYdhe GdbOjeI ef JUGfja GdjhfGf hGdaQS hGdgfO GdehLhO efgG HdZI GdYQH hgh CQHYI ebGdGJ GdebGdI GdChdi CQHYI afhf s
(3BNQgG (B:s
(3cJGH GdCeGd Ydi QCS GdchQ bGd eMeO Hf ZSMb hGdcJH GdeDda ai gPG GdTCf CcKQ hCYXe ef Cf JMUi JeJ GdebGdI GdQGHYI ef cJGH GdagQSJ hHJeGegG Je LejY GdcJGH hGddg GdMeO hGdefg hGdMhd hGdbhI hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hSde JSdjekG s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B29 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B41s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs